2020
DOI: 10.1111/desc.13038
|View full text |Cite
|
Sign up to set email alerts
|

Partner in crime: Beneficial cooperation overcomes children’s aversion to antisocial others

Abstract: Young children display strong aversion toward antisocial individuals, but also feel responsible for joint activities and express a strong sense of group loyalty. This paper aims to understand how beneficial cooperation with an antisocial partner shapes preschoolers’ attitudes, preferences, and moral judgments concerning antisocial individuals. We argue that although young children display a strong aversion to antisocial characters, children may overcome this aversion when they stand to personally benefit. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…And, infants give up resources to interact with someone who helps others rather than harms others (Tasimi & Wynn, 2016). At 2 years of age, children prefer to help those who have helped others over those who have harmed others (Dahl et al, 2013), and by 4 years, children preferentially choose and distribute resources to partners whose bad action benefitted the child (compared to when it did not benefit the child; Myslinska Szarek et al, 2020). Combined, these results demonstrate early-emerging sensitivity to others' behavior in infants' and young children's social evaluations (especially choices between two agents).…”
Section: The Development Of Punishment and Partner Choice Decisions In Childhoodmentioning
confidence: 99%
“…And, infants give up resources to interact with someone who helps others rather than harms others (Tasimi & Wynn, 2016). At 2 years of age, children prefer to help those who have helped others over those who have harmed others (Dahl et al, 2013), and by 4 years, children preferentially choose and distribute resources to partners whose bad action benefitted the child (compared to when it did not benefit the child; Myslinska Szarek et al, 2020). Combined, these results demonstrate early-emerging sensitivity to others' behavior in infants' and young children's social evaluations (especially choices between two agents).…”
Section: The Development Of Punishment and Partner Choice Decisions In Childhoodmentioning
confidence: 99%
“…Finally, recent research has shown that when young children collaborate with partners who help them acquire resources but also harm third parties, their obligation to sustain the beneficial relationship is stronger than their aversion to antisocial others. In the result, children express a positive attitude towards the partner, even though they recognize the partner's actions as immoral (Myslinska-Szarek, Bocian, Baryla, & Wojciszke, 2020). Therefore, we propose that children's sociomoral judgements of individuals who harm others depend on the social and relational context in which antisocial behaviour occurs.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, a recent study has demonstrated that young children like individuals who harm antisocial characters (vs. prosocial or neutral) and, therefore, judge their behavior as less bad . Finally, although young children display a strong aversion toward antisocial individuals, research has shown that beneficial cooperation (vs. nonbeneficial) with an antisocial partner increases children's liking and preference for the antisocial partner (Myslinska-Szarek et al, 2021).…”
Section: Interpersonal Attitudes Bias Moral Cognitionmentioning
confidence: 99%